PENERAPAN PROSES PENGGAJIAN MENGGUNAKAN PAYROLL DIGIBANK DI PT BAM SOLUSINDO SEJAHTERA - Indra Safei (2021)
This Final Project Report was made to find out the understanding of how to implement the payroll process using payroll at the bank. The payroll process using payroll in the world of work is very important to do and also has the specific purpose of writing this final project, namely as a requirement for graduation from the Diploma Three program for the accounting department of the Jakarta Veterans National Development University. The author conducts Field Work Practice (PKL) at PT BAM Solusindo Sejahtera in the Finance Accounting section. The payroll process for making payroll at PT BAM Solusindo Sejahtera is one of the routine activities that occurs once a month at the time of payroll which is carried out by the Finance Accounting section. At the end of each month, the section always prepares the calculation of employee salaries and the employee salary list which is always changing because of the frequent entry and exit of employees as sales. The calculation of the salary will be submitted to the directors and commissioners as shareholders. After receiving approval, the payroll process will be processed by the Finance Accounting section at the beginning of the month.